Notch1 promotes resistance to cisplatin by up-regulating Ecto-5′-nucleotidase (CD73) in triple-negative breast cancer cells - Yuzhu Qi; Meifang Li; Shaozhong Li; De Zeng; Yingsheng Xiao; Jiwei Li; Qianqian Ye; Edwin Bremer; Guo-jun Zhang (Cell Death Discovery, 2023)
Abstract Triple-negative breast cancer (TNBC) is an aggressive molecular subtype that due to lack of druggable targets is treated with chemotherapy as standard of care. However, TNBC is prone to chemoresistance and associates with poor survival. The aim of this study was to explore the molecular mechanisms of chemoresistance in TNBC. Firstly, we found that the mRNA expression of Notch1 and CD73 in cisplatin-treated patient material associated with poor clinical outcome. Further, both were upregulated at the protein level in cisplatin-resistant TNBC cell lines. Overexpression of Notch1 intracellular domain (termed N1ICD) increased expression of CD73, whereas knockdown of Notch1 decreased CD73 expression. Using chromatin immunoprecipitation and Dual-Luciferase assay it was identified that N1ICD directly bound the CD73 promoter and activated transcription. Taken together, these findings suggest CD73 as a direct downstream target of Notch1, providing an additional layer to the mechanisms underlying Notch1-mediated cisplatin resistance in TNBC.